1981
DOI: 10.1139/f81-060
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Behavior of Hybrid Charr (Salvelinus fontinalis × S. namaycush)

Abstract: Observations of the reproductive behavior of splake (Salvelinus fontinalis × S. namaycush) planted in Jack Lake, Algonquin Park, Ont., indicated that they spawned on rocky shoals from late October to early November. In mid-October, splake approached the spawning locations. By late October females had selected redd sites and dominant males were aggressively defending the sites that had been cleared by the females, against other males. Redd digging was variable in duration and frequency. Depth of water over redd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…In a study with Salvelinus fontinalis×S. namaycush hybrids, Berst et al (1981) reported that different sound frequencies were associated with distinct behaviours such as female diggings and pair spawning quiverings. Salmonids are thought to have very poor hearing-they are only Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with Salvelinus fontinalis×S. namaycush hybrids, Berst et al (1981) reported that different sound frequencies were associated with distinct behaviours such as female diggings and pair spawning quiverings. Salmonids are thought to have very poor hearing-they are only Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This idea, based on the supremacy of large dominating males in the spawning grounds, only allowed females a passive role in spawning activity. Nevertheless, females have been reported to exhibit their choice by frequently attacking smaller males (Berst et al, 1981;Keenleyside and Dupuis, 1988b;Ja¨rvi, 1990;Petersson and Ja¨rvi, 1997;Berejikian et al, 1997), and by delaying spawning when courted by nondesirable males (Schroder, 1981;Foote, 1988Foote, , 1989Foote and Larkin, 1988;Blanchfield and Ridgway, 1999;Berejikian et al, 2000;Gaudemar et al, 2000b). Delaying spawning is a form of choice by which females increase their chances of being joined by larger or more fit males.…”
Section: Overview Of the Salmoninae Mating Systemmentioning
confidence: 99%
“…To do so he maintains a backward position and constantly passes over her caudal peduncle from side to side trying to guard her from males coming from either side. This conduct has been called ''crossover'' (Tautz and Groot, 1975;Berst et al, 1981;Berejikian et al, 1997;Gaudemar et al, 2000b). Crossover behaviour possibly contributes to courting due to constant stimulation of the female's dorsal area (personal observations).…”
Section: Nest Probingmentioning
confidence: 99%
“…No information on the level of phylogenetic relationships between S. namaycush and S. fontinalis is available to us. However, existence of hybrid forms traced up to F 4 by Berst et al [66] and entering reproductive relations indicate close relations between these two North-American species. Molecular data by Westrich et al [67] also are in favor of this assumption.…”
Section: Resultsmentioning
confidence: 99%